2020
DOI: 10.1186/s12864-020-07180-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals mechanism of early ripening in Kyoho grape with hydrogen peroxide treatment

Abstract: Background In a previous study, the early ripening of Kyoho grape following H2O2 treatment was explored at the physiological level, but the mechanism by which H2O2 promotes ripening at the molecular level is unclear. To reveal the molecular mechanism, RNA-sequencing analysis was conducted on the different developmental stages of Kyoho berry treated with H2O2. Results In the comparison of treatment and control groups, 406 genes were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 110 publications
3
20
0
Order By: Relevance
“…In fact, the endogenous ripening related ROS production does not result in the cell wall and growth inhibition, as this production is suspected to occur just before or at the inception of the second fruit growth phase. Indeed, recent physiological and transcriptomic works evidenced that the less harmful hydrogen peroxide (H 2 O 2 ) accelerated ripening in Kyoho variety 31 , 32 . The genes suggested by the authors to induce the early ripening were associated with the oxidative stress, photosynthesis, cell wall deacetylation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the endogenous ripening related ROS production does not result in the cell wall and growth inhibition, as this production is suspected to occur just before or at the inception of the second fruit growth phase. Indeed, recent physiological and transcriptomic works evidenced that the less harmful hydrogen peroxide (H 2 O 2 ) accelerated ripening in Kyoho variety 31 , 32 . The genes suggested by the authors to induce the early ripening were associated with the oxidative stress, photosynthesis, cell wall deacetylation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, six commonly used endogenous reference genes ( Actin , GAPDH , VvEF1‐α , VvEF1‐γ , EF1‐α and Ubiquitin ) were first selected according to previously published reports (Costantini et al 2008, Gamm et al 2011, Szegedi et al 2018). In addition to those genes, three novel genes (named RRM1 , PPR2 and MRE11 ) were screened from our previous RNA‐sequencing data (Guo et al 2016, 2019a,b, 2020, Wang et al 2019c), in which we demonstrated stable expression patterns in grape berry at different developmental stages and under H 2 O 2 , riboflavin and 5‐azaC treatments (Figure 1). Based on the annotations and references, these three genes have unknown functions in grapevine with RRM1 encoding heterogeneous nuclear ribonucleoprotein, PPR2 encoding pentatricopeptide repeat‐containing protein and MRE11 encoding double‐strand break repair protein (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In brief, the nine berry developmental stages followed the modified Eichhorn and Lorenz developmental scale (Coombe 1995) from 19 May to 13 August in 2013. The treatments of H 2 O 2 , riboflavin and 5‐azaC (5‐azacytidine) were conducted on Kyoho berries according to the previous studies (Guo et al 2019a,b, 2020, Wang et al 2019c). A volume of 20 mL H 2 O 2 solution (300 mmol/L) was sprayed evenly on each berry bunch twice (25 and 35 days post‐anthesis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the endogenous ripening related ROS production does not result in the cell wall and growth inhibition, as this production is suspected to occur just before or at the inception of the second fruit growth phase. Indeed, recent physiological and transcriptomic works evidenced that the less harmful hydrogen peroxide (H 2 O 2 ) accelerated ripening in Kyoho variety 29,30 . The genes suggested by the authors to induce the early ripening were associated with the oxidative stress, photosynthesis, cell wall deacetylation and degradation.…”
Section: Discussionmentioning
confidence: 99%